Inducing panchromatic absorption and photoconductivity in polycrystalline molecular 1D lead-iodide perovskites through π-stacked viologens - Febriansyah, Benny (2020)
As a consequence of their quantum- and electronically-confined inorganic lattices, molecular 1D lead-iodide perovskites are ill suited to photovoltaic (PV) applications. In order to circumvent these problems, we utilized electron accepting viologen (N,N′-dialkyl-4,4′-bipyridinium) dications incorporating hydrogen bond donor functionalities, which served to induce π–π stacking interactions. The resulting ‘viologen dimers’ display enhanced charge-transfer (CT) interactions with the 1D lead-iodide nanowires. This manifests in extended light absorption (up to 800 nm), reduced band gaps (1.74 eV to 1.77 eV), and longer photoluminescence lifetimes. More importantly, we demonstrate significant photoconductivity behavior in polycrystalline molecular 1D lead-iodide perovskites for the first time. Thus, this work offers a strategy for inducing the properties required for PV applications in molecular 1D lead-iodide perovskites.